CLINICAL OUTCOMES OF ALTEPLASE IN ACUTE ISCHEMIC STROKE PATIENTS AT NAN HOSPITAL - Kuariyakul, Nalinorn; Boonmuang, Pornwalai; Suphanklang, Juthathip (Thai Bulletin of Pharmaceutical Sciences, 2021)
The trend of ischemic stroke in Thailand has increased. Alteplase is registered as a thrombolytic agent for the treatment of acute ischemic stroke, in case of an onset of symptoms is not more than 3-4.5 hours. This study aimed to determine the clinical outcomes of alteplase in acute ischemic stroke patients. This study was a retrospective cohort study that was conducted among acute ischemic stroke patients admitted at Nan hospital between January 2012 and December 2019. A total of 246 patients were included. There were classified to one hundred and forty-two patients were in alteplase group and 104 patients were not received alteplase. The results showed that at 24 hours, 48.94% of patients in alteplase group had a favorable outcome (NIHSS score was declined greater than or equal to 4 points) compared with 26.51% in patients without alteplase [OR 2.66 (95%CI 1.48-4.97), p-value = 0.001]. When followed up at 1, 3 and 6 months the results showed that good clinical outcomes (Barthel index was greater than or equal to 95 points) did not significantly different between the alteplase and non-alteplase groups [OR 1.69 (95%CI 0.88-3.23), p-value=0.140, OR 1.54 (95%CI 0.71-3.38), p-value=0.322 and OR 2.14 (95%CI 0.93-4.93), p-value=0.091), respectively]. But the number of patients treated with alteplase who had Modified Rankin Scale 0-1 at discharge was significantly higher than those treated without alteplase [OR 3.40 (95%CI 1.76-6.54, p-value =0.000)]. In terms of side effect, the percentage of intracerebral hemorrhage was higher in alteplase group (19.01%) than non-alteplase group treated (2.88%), statistically significant [OR 7.90 (95% CI 2.33-26.84, p-value =0.000)]. Therefore, alteplase in acute ischemic stroke patients could reduce severity and disability of the patients. However, intracerebral hemorrhage should be closely monitored.